Thuật toán tính mật độ điện tích thứ cấp trên ranh giới bất đồng nhất - Hoa, Tạ Quỳnh; Minh, Vũ Đức (Vietnam Journal of Earth Sciences, 2004)
The Algorithm for calculating density of secondary electrics on the unhomogeneous boundary